Coastal Area Development Through Mangrove Planting and Tree Foster Parents as Climate Change Restoration and Mitigation Efforts Sedari Village, Cibuaya District, Karawang Regency - Ismail, Taufik; Andhika Putra, M.; Insani M, Cita (International Journal of Science, Technology & Management, 2022)
The global community is faced with a number of problems such as the climate crisis. The coastal area is one area that is vulnerable to abrasion and the impact of the climate crisis. Sedari Village is one of the areas on the coast that has the risk of abrasion and climate change. Therefore, PT Pertamina Patraniaga Cikampek BBM Terminal carries out a coastal area development program through planting mangroves and foster parent trees. Community empowerment activities aim to map the activities needed for environmental restoration. Within the framework of management science in general, activities consist of planning, organizing, implementing, and evaluating. Within the framework of management science in general, activities consist of planning, organizing, implementing, and evaluating. Based on community empowerment activities, it is concluded that coastal area development activities through mangrove planting and OTAP initiation have a high urgency value. then the activity is a collaboration between communities based on academic, industrial, community, government and media groups.